2015
DOI: 10.3171/2014.10.jns141576
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hemodynamic disturbance in dural arteriovenous fistula with retrograde leptomeningeal venous drainage: a prospective study using 123I-iodoamphetamine single photon emission computed tomography

Abstract: abbreviatioNs ACR = affected-to-contralateral side asymmetry ratio; CBF = cerebral blood flow; CVR = cerebral vascular reactivity; dAVF = dural arteriovenous fistula; DSA = digital subtraction angiography; DTARG = dual-table autoradiographic; HIA = high-intensity area; IMP = iodoamphetamine; QSPECT = quantitative SPECT; rCBF = regional CBF; RLVD = retrograde leptomeningeal venous drainage; ROI = region of interest; SPECT = single photon emission computed tomography; TAE = transarterial embolization; TVE = tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Indeed, SPECT studies have been done in patients with dAVF; however, all of them have reported hypoperfusion. 9,10…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, SPECT studies have been done in patients with dAVF; however, all of them have reported hypoperfusion. 9,10…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The present results, a high rSI of the veins with CVR was strongly correlated with aggressive DAVF behavior, may indirectly reflect the fact that severe venous hypertension causes cerebral hemodynamic and metabolic disturbances. [7][8][9]19 Intracranial DAVFs with CVR have been associated with a high incidence of serious adverse events and poor outcomes. 6 However, in recent years, lower adverse event rates have been reported for asymptomatic DAVFs with CVR, 5,20 and symptomatic CVR has been considered an important factor for severe neurological events.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have evaluated cerebral hemodynamics and cerebral metabolism in patients with intracranial DAVFs with CVR using positron emission tomography, single photon emission computed tomography, perfusion MRI, arterial spin labeling perfusion imaging, and MR spectroscopy. [7][8][9][10][11]19,25 These reports have indicated that accompanying CVR can lead to reduced regional cerebral blood flow, increased cerebral blood volume, elevated regional oxygen extraction fraction, and impaired cerebral circulation and metabolism. [9][10][11]19 Therefore, imaging follow-up with several modalities is essential for identifying the changes associated with aggressive DAVF behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations